Evolutionary engineering and characterization of Sendai virus mutants capable of persistent infection and autonomous production - Iwata, Moe; Kawabata, Ryoko; Morimoto, Nao; Takeuchi, Ryosuke F.; Sakaguchi, Takemasa; Irie, Takashi; Osakada, Fumitaka (Frontiers in Virology, 2024)
Persistent virus infection involves modifying the host immune response and maintaining viral infection. Acute infection with Mononegavirales, such as Sendai viruses (SeVs), can give rise to viruses capable of persistent infection. SeVs establish persistent infection through generating copyback-type defective interfering (cbDI) genomes or acquiring temperature-sensitive mutations. Herein, we identify novel mutations associated with persistent infection and recombinant SeV mutants capable of persistent infection and autonomous production at physiological body temperature, independent of cbDI genomes or temperature-sensitive mutations. Diverse SeV populations were generated by passing the cDNA-recovered SeV Z strain nineteen times through embryonated chicken eggs and subsequently infecting LLC-MK2 cells with the SeV populations to finally obtain SeV mutants capable of persistent infection and autonomous production in several types of cultured cells. Sequence analysis identified four or five mutations in the genome of the persistently infectious SeVs, distinguishing them from other existing strains with persistent infection. Recombinant SeVs carrying four or five mutations in the Z strain genome (designated SeV-Zpi or SeV-Zpi2, respectively) exhibited persistent infection and autonomous production in LLC-MK2, BHK-21, and Neuro2a cells at 37°C. SeV-Zpi and SeV-Zpi2 consistently produced viral particles even after long-term passages without cbDI particles or temperature-sensitive phenotypes. These results highlight the ability of acute infections of SeVs to spontaneously acquire mutations during replication, thereby endowing persistent infection and autonomous production at body temperature. The vectorization of SeV-Zpi and SeV-Zpi2 will contribute to both basic research and medical applications.